Features of Criminal Proceedings (Pre-Trial and Trial Investigation) in the Time of Pandemic Covid-19 - Бєлік, Лариса Степанівна; Бєлік, Л. С.; Белик, Лариса Степановна; Bielik, Larysa S.; Самойленко, Олена Анатоліївна; Самойленко, О. А.; Самойленко, Елена Анатольевна; Samoilenko, Olena A.; Мудрецька, Ганна Володимирівна; Мудрецька, Г. В.; Мудрецкая, Анна Владимировна; Mudretska, Hanna V.; et al. (Universidad de Los Hemisferios, 2020)
The work is devoted to the main problems and features that have emerged in the field of criminal justice (pre-trial investigation and trial) in a pandemic. The relevance of this article is that criminal justice, like other areas of human activity, has been affected after the spread of Covid-19 and its recognition as a pandemic. The introduction of quarantine was accompanied by some problematic issues, including uncertainty in the work of the judiciary and law enforcement agencies, lack of a unified approach to court schedules, and the conduct of certain investigative actions. Thus, it is necessary to analyze the peculiarities of criminal proceedings in a pandemic. An explorative and collative methodology (that considers the comparative law) was used. The proposals have been made to address the problems that arise during the pre-trial investigation and criminal proceedings in a pandemic, in particular: the need to allow videoconferencing in criminal proceedings out of court; a list of programs for video communication have been defined; to provide adequate funding for technical re-equipment; to suspend the terms of criminal proceedings, and; to prevent in the future the situation of cancellation of previously adopted decisions on the strengthening of criminal liability for intentional infection.

Робота присвячена основним проблемам та особливостям, що виникли у сфері кримінального судочинства (досудового слідства та суду) в умовах пандемії. Актуальність цієї статті полягає в тому, що кримінальне судочинство, як і інші сфери людської діяльності, постраждало після поширення Covid-19 та визнання його пандемією. Запровадження карантину супроводжувалося деякими проблемними моментами, серед яких невизначеність у роботі судових та правоохоронних органів, відсутність уніфікованого підходу до розкладів судових засідань, проведення окремих слідчих дій. Таким чином, необхідно проаналізувати особливості кримінального провадження в умовах пандемії. Використовувалась дослідницька та колативна методологія (з урахуванням порівняльного правознавства). Внесено пропозиції щодо вирішення проблем, що виникають під час досудового розслідування та кримінального провадження в умовах пандемії, зокрема: необхідність дозволу відеоконференц-зв’язку у кримінальному провадженні у позасудовому порядку; визначено перелік програм для відеозв'язку; необхідність забезпечення достатнього фінансування на технічне переозброєння; зупинити строки кримінального провадження та не допустити в майбутньому ситуації скасування раніше прийнятих рішень щодо посилення кримінальної відповідальності за умисне зараження.
Bielik L. Features of criminal proceedings (pre-trial and trial investigation) in the time of pandemic COVID-19 / L. Bielik, O. Samoilenko, H. Mudretska, T. Voloshanivska, K. Titunina // Ius Humani. Revista de derecho. - Vol 9. - № 2. - Universidad de Los Hemisferios, 2020. – P. 203-224.
Keywords: criminal proceedings; Covid-19; pre-trial investigation; quarantine; human rights and freedoms; кримінальні провадження; Covid-19; досудове розслідування; карантин; права і свободи людини; Research Subject Categories::LAW/JURISPRUDENCE